The Effect of Debt to Equity Ratio, Return on Equity and Earnings Per Share on Financial Profitability in the Property Sector Listed on the Indonesia Stock Exchange - Yulanda, Siti Ayu; Suhardi, Suhardi; Napisah, Siti (Economic: Journal Economic and Business, 2025)
This research seeks to examine the impact of Earnings per Share (EPS) on a firm's financial performance, which is assessed through Return on Assets (ROA) and share price. EPS serves as a crucial metric of profitability on a per-share basis, which is posited to influence investor perceptions and the efficacy of asset utilization within the company. The study employs a quantitative methodology utilizing linear regression analysis, drawing upon secondary data from the annual financial reports of non-financial sector firms listed on the Indonesia Stock Exchange (IDX) for the period spanning 2020 to 2023. The findings indicate that EPS exerts a positive and significant influence on both ROA and share price, suggesting that an enhancement in earnings per share aids in asset efficiency in profit generation and elevates the firm's market valuation. Nonetheless, the research also underscores that EPS should not be viewed in isolation as the exclusive determinant of financial performance, as external factors such as market dynamics and investor sentiment also play a significant role. These results hold implications for corporate management and investors in the realm of strategic decision-making. Further research is encouraged to incorporate additional financial metrics as well as non-financial elements to render the findings more holistic.